Factors Affecting the Success of Agile Software Teams - Ayat Ragab Moustafa; Mohie Ghalab Abdulrasoul (المجلة الدولية للحاسبات والمعلوماتية, 2024)
Thousands of teams are using agile software development methods, especially Scrum. Few of them are really “living” Scrum and therefore successful. This paper discusses the factors that led the Scrum team to the successful. A survey about the success factors in agile projects especially that related to the Scrum teams is presented. We proposed a new framework for the success factors of the Scrum team. According to a questionnaire is distributed to evaluate the Scrum team performance, we concluded that some of the success factors are strongly or moderated applied, but others are applied with a low degree. We calculated the Adherence degree for each success factor according to our evaluation to know its importance in the success of the software project.